2016
DOI: 10.3390/nu8030138
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Administration of Lycopene, a Tomato Extract, Protects against Myocardial Ischemia-Reperfusion Injury

Abstract: Background: Oral uptake of lycopene has been shown to be beneficial for preventing myocardial ischemia-reperfusion (I/R) injury. However, the strong first-pass metabolism of lycopene influences its bioavailability and impedes its clinic application. In this study, we determined an intravenous (IV) administration dose of lycopene protects against myocardial infarction (MI) in a mouse model, and investigated the effects of acute lycopene administration on reactive oxygen species (ROS) production and related sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…The main effect of lycopene and tomato supplementation is the reduction of oxidative stress, and besides being a potent scavenger of singlet oxygen and peroxyl radicals, lycopene modulates the production of antioxidant enzymes through the Nrf-2 pathway. Indeed, Tong et al [10] investigated the effects of acute lycopene administration on oxidative stress in both in vitro and in vivo ischemia-reperfusion injury models. The authors showed that lycopene treatment before reperfusion reduced cardiomyocyte death, ROS production and JNK phosphorylation in the cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main effect of lycopene and tomato supplementation is the reduction of oxidative stress, and besides being a potent scavenger of singlet oxygen and peroxyl radicals, lycopene modulates the production of antioxidant enzymes through the Nrf-2 pathway. Indeed, Tong et al [10] investigated the effects of acute lycopene administration on oxidative stress in both in vitro and in vivo ischemia-reperfusion injury models. The authors showed that lycopene treatment before reperfusion reduced cardiomyocyte death, ROS production and JNK phosphorylation in the cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Lycopene is the main fat-soluble pigment responsible for the red color of ripe tomatoes. In vitro and in vivo studies have shown that lycopene acts as a potent antioxidant [9,10]. It is the most efficient scavenger of singlet oxygen and peroxyl radicals among the carotenoids, and it modulates the production of antioxidant enzymes, such as superoxide dismutase (SOD) and catalase (CAT), mainly due to their actions on nuclear factor E2-related factor 2 (Nrf2) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to stress that the Mediterranean diet also allows the intake of fat-soluble antioxidants, among which carotenoids, such as lutein, zeaxanthin, astaxanthin, -carotene, -carotene, lycopene, etc., are certainly one of the most well represented groups in foods of vegetal origin [4]. Several studies indicated that these compounds, due to their capacity to scavenge reactive oxygen species (ROS) [5], may exert beneficial effects in different pathological states characterized by increased ROS production, such as neurodegenerations [6], myocardial ischemia [7], diabetic retinopathy [8].…”
Section: Introductionmentioning
confidence: 99%
“…They present a complex pathogenesis, the majority of them being caused by ischemic events and, globally, they can be considered as the result of a sum of different complementary factors, such as increased blood lipid levels and blood pressure, as well as endothelial dysfunction (Gonzalez & Selwyn, 2003). Although nowadays there are numerous technical interventions that can be conducted in order to treat patients, such as coronary bypass surgery, thrombolysis, or angioplasty (Tong et al, 2016), special attention must be taken regarding primary prevention, since this group of diseases is mainly caused by modifiable risk factors. Among them, perhaps the most important one is diet.…”
Section: Pathophysiology Of Cardiovascular Diseasementioning
confidence: 99%
“…In the context of cardiovascular ischemic diseases, it is also important to considerer that reperfusion after prolonged ischemia may lead to myocardial injury, which, in turn, can cause infarct expansion and/or arrhythmias (Tong et al, 2016). However, either in the case of the initial lesion, or in the case of reperfusion lesions, oxidative stress appears to have a central role (Tong et al, 2016). Thus, high antioxidant levels, including those of lycopene, may contribute in preventing or, at least, decreasing, the extent of these lesions.…”
Section: Pathophysiology Of Cardiovascular Diseasementioning
confidence: 99%